KESEPADANAN MAKNA DALAM TERJEMAHAN LIRIK LAGU LEAD THE WAY KARYA JHENÉ AIKO DAN KITA BISA KARYA ADRIAN WAROUW - Praftina, Alinda Tyas; Ramadhanti, Aulia; Salsabiila, Fardha Yoedya; Kusumastuti, Fenty (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research focuses on the similarity in meaning between the lyrics of the song Bsu (Lead The Way) and Bsa (We Can). This research uses descriptive qualitative research methods. The theory used in this research is J.S.'s category shift theory. Catford (1965). The data used in this research are the lyrics of the song Lead The Way and the lyrics of the song Kita Bisa. The research data source was taken from the DisneyMusicVevo YouTube channel as source language data and the DisneyMusicAsiaVevo YouTube channel as target language data. The results of research on the equivalence of meaning in the translation of the lyrics of the song Lead The Way into Kita can be found in several types of category shifts by the category shift theory by Catford (1965). The types of shifts that occur are intra-system shifts, unit shifts, structure shifts, and class shifts.